Essays in empirical asset pricing - Cai, Haidong (2021)
The thesis encompasses three essays in empirical asset pricing and mainly concentrates on Chinese stock and futures markets. Traditional asset pricing models assume the arrival of information is immediately processed and incorporated into asset prices. In reality, there are numerous constraints that may distort the assumption, for instance the cross-border transmission and the cognitive limitation of humans. The three essays specifically explore the impact of these issues on asset prices.